2021
DOI: 10.1002/ijgo.14041
|View full text |Cite
|
Sign up to set email alerts
|

“So hard not to feel blamed!”: Assessment of implementation of Benin’s Maternal and Perinatal Death Surveillance and Response strategy from 2016–2018

Abstract: Objective To assess the implementation of the Maternal and Perinatal Death Surveillance and Response (MPDSR) strategy institutionalized in Benin in 2013 to address the alarmingly high maternal and neonatal death rates. Methods A retrospective, mixed‐methods study was performed. We used all maternal and neonatal death notifications and reviews from 2016 to 2018, reviewed the reports of 63 MPDSR working groups, and held two online group discussions. Descriptive quantitative analysis was performed, and content an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Using pre-post designs with interviews and focus groups, the role of leadership in facilitating QI was reported by Limato and colleagues [ 70 ] in Indonesia and Nahimana and colleagues [ 84 ] in Rwanda where leaders owned and steered interventions. In contrast, Hounsou and colleagues [ 89 ] using mixed methods reported that a lack of interest by managers constrained MPDSR in Benin. Senior leaders, especially, need to actively embrace and publicly show support for QI for it to succeed as health workers do not wish to second guess their bosses’ allegiances [ 43 , 56 , 64 , 69 , 77 , 82 ].…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Using pre-post designs with interviews and focus groups, the role of leadership in facilitating QI was reported by Limato and colleagues [ 70 ] in Indonesia and Nahimana and colleagues [ 84 ] in Rwanda where leaders owned and steered interventions. In contrast, Hounsou and colleagues [ 89 ] using mixed methods reported that a lack of interest by managers constrained MPDSR in Benin. Senior leaders, especially, need to actively embrace and publicly show support for QI for it to succeed as health workers do not wish to second guess their bosses’ allegiances [ 43 , 56 , 64 , 69 , 77 , 82 ].…”
Section: Resultsmentioning
confidence: 95%
“…Researchers overwhelmingly focused on topics related to improvements in maternal and child health (MCH) with twenty-nine studies, including some two conducted in Kenya [ 46 , 79 ] and some five that focused on maternal and perinatal deaths: in Ethiopia [ 63 ]; in Benin [ 89 ]; in South Africa [ 65 ]; in Rwanda [ 64 ] and in Rwanda, Tanzania, Zimbabwe and Nigeria [ 62 ]. A summary of studies by topic of focus is contained in supplementary files ( S3 Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Review of maternal death is a key part of MDSR. Maternal death reviews were not carried out routinely and were irregular in most countries [7][8][9][10][11][13][14][15][16] or stopped completely. 12 One healthcare provider noted that financial resources were not available to conduct reviews, which prevented them from happening.…”
Section: Implementing Maternal Death Surveillance and Response In Sub...mentioning
confidence: 99%
“…Notification of maternal death is incorporated into routine health management information systems via integrated disease surveillance and response systems in Benin, 7 Burkina Faso, 8,9 Cameroon, 10 Central African Republic, 11 Chad, 12 Ghana, 13 and Liberia 14 . However, most of the countries continue to underreport maternal and neonatal deaths 12 and many countries do not include neonatal deaths in the notification system 15 .…”
mentioning
confidence: 99%